Quantifying the costs of sovereign defaults using odious debt cases as a quasi-natural experiment - Fabian Horn (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Sovereign defaults enable the defaulting countries to eliminate its debt, which raises the question why sovereign debt can exist, given that lenders fear losing their money. Thus, a cost burden must exist for a country in order to achieve the government paying its debt. Historically, sovereign defaults mostly occur in times of low GDP growth rates. This makes it impossible to isolate the defaults impact on macroeconomic fundamentals since the vice-versa causality cannot be ruled out when a traditional regression analysis is applied. With this, it is not conceivable to quantify the defaults idiosyncratic costs. An instrument variable for a sovereign default has not been found and it is likely that such an instrument does not exist at all. This paper applies a natural experiment approach to circumvent the above mentioned causality problem. Odious debt cases, as well as scenarios where the government leaders have argued that the government debt is illegitimate, are applied to quantify the sovereign default s impact on macroeconomic fundamentals. Since only few of these cases are available, a panel analysis is conducted, using the Abadie and Gardeazabal (2003) and Abadie et al. (2010) synthetic control method for comparative case studies, in order to generate synthetic counterfactual countries that have the same macroeconomic fundamentals in the pre-default period. In addition to that, the creditors behavior towards the defaulting country is analyzed, giving hints that the GDP, FDI s, private lending as well as development aid may decline after the non-necessary default is announced.
Keywords: C82; F34; F51; 330